Arcabouço biorreabsorvível de poli(L-co-D,L ácido láctico-co-trimetileno carbonato) cultivado com célula-tronco mesenquimal direcionada à regeneração óssea: estudo in vitro e in vivo - Asami, Jessica (2020)
Degenerative and bones inflammatory problems represents almost half of chronic diseases developed on people older than 50 years old around the world, leading to problems of prolonged pain and physical limitation. Its prevalence increases with age and life style, therefore, with elderly population growth, these cases have been increasing too. These problems resolution, usually demand surgeries which involve implant and bone graft. Even with these therapeutic solution success, some inconvenient have been appearing, because of the fact implants are susceptible to infections, and because of grafts can lead to severe pain, local tissue death, and immunological rejection. Aiming to solve these limitations, Tissue engineering have appeared as an promising field of bone wound repair and reconstruction, through tridimensional porous matrix development, usually designated as scaffolds. Associated to these structures, are osteoprogenitors cells and growth factors, which lead to new bone tissue growth, through stimulation of ability of natural tissue regeneration of patient. Aiming this important clinical gap, the biomaterial Poly(L-co-D,L lactic acid- co-Trimethylene Carbonate) (PLDLA-TMC) presents advantageous features to the medical field, mainly when related to stem cells, due to immunemodeling activities of this cells. Therefore, in this essay it was seeding in a PLDLA-TMC 3D scaffold with different pores sizes (300 e 600 µm) for proliferation and ostegenic differentiation. In vivo assay were used 36 Wistar rats and were made a cranial bone defect with 8 mm diameter, separeted in 3 groups: negative control, group with PLDLA-TMC and group with PLDLA-TMC+MSC, in periods of 8 and 12 weeks. The results in vitro assay obtained for analysis by Laser Scanning Confocal Microscopy (LSCM) showed that PLDLA-TMC 3D scaffolds with 600 µm pore size, when compared the sacaffold of 300 µm pore size, favored the adherence and cell growth, and mainly, presented osteoinductive characteristic, which means that the material itself inducted cellular differentiation. The scaffolds implants of PLDLA-TMC with MSC, through histological and microCT analisys, showed better results in the period of 12 weeks, obtainning less inflammatory process and greater regeneration of bone tissue.